2015
DOI: 10.1016/j.compedu.2014.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Technology tools to support learning design: Implications derived from an investigation of university teachers' design practices

Abstract: The need to improve the quality of higher education has fostered an interest in technology tools to support effective design for teaching and learning. Over the past decade this interest has led to the development of tools to support the creation of online learning experiences, specifications to underpin design systems, and repositories to share examples. Despite this significant activity, there remain unanswered questions about what shapes university teachers' design decisions and how tools can best support t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
2
11

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(121 citation statements)
references
References 25 publications
(27 reference statements)
5
103
2
11
Order By: Relevance
“…Thus, there is an increasing interest to align LA with LD, as the former facilitates the transfer of tacit educational practice to an explicit rendition, while the latter provides educators with pedagogical context for interpreting and translating LA findings to direct interventions [10][11][12][13][14]. While there are abundant discussions on the value and impact of integrating LD into LA to improve teacher inquiry [13,14], only a few studies have empirically examined how teachers actually design their courses [15,16] and whether LD influences satisfaction, VLE behavior, and retention [9,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is an increasing interest to align LA with LD, as the former facilitates the transfer of tacit educational practice to an explicit rendition, while the latter provides educators with pedagogical context for interpreting and translating LA findings to direct interventions [10][11][12][13][14]. While there are abundant discussions on the value and impact of integrating LD into LA to improve teacher inquiry [13,14], only a few studies have empirically examined how teachers actually design their courses [15,16] and whether LD influences satisfaction, VLE behavior, and retention [9,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In an interview-based study of 30 instructors, Bennett, Agostinho and Lockyer [3] identified student-related factors (e.g., cohort profile, learning objectives, feedback from past sessions) as one of the key factors (together with instructorsrelated factors and context-related factors) that influenced how instructors engaged in the design process.…”
Section: Introductionmentioning
confidence: 99%
“…Advindo da pesquisa em tecnologia educacional, o uso do learning design destina-se a apoiar professores universitários na elaboração de atividades online com seus alunos, de maneira que propiciem experiências de aprendizagem autêntica (Bennett, Agostinho & Lockyer, 2015). Alguns autores destacam ferramentas baseadas em tecnologia para dar suporte ao processo de design e criação de repositórios online para compartilhamento de exemplos e práticas de learning design (Agostinho, 2011;Conole & Culver, 2009).…”
Section: Learning Designunclassified